Pendampingan Deteksi Dini Kanker Payudara melalui Komunikasi Informasi dan Edukasi (KIE) di SMP Muhammadiyah 8 Surakarta - Kusumawati, Yuli; Faiza, Salsabila Alif; Khoirunisa, Ilma; Zulaekah, Siti (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Breast cancer is the leading cause of death for some women and currently ranks first among cancers that attack women. Not a few adolescent girls aged 14 years and above have been indicated to have breast cancer. This activity aims to provide educational communication and information (KIE) about breast cancer to female students of SMP Muhammadiyah 8 Surakarta. Method: The community service was held at SMP Muhammadiyah 8 Surakarta, targeting female students. The techniques used are education and socialisation as well as providing direct training to female students about breast cancer and early detection. 36 female students participated in the community service. Results: The results of the community service show that the average pre-test score is 4.972 and the average post-test score is 6.194 with a significance value of 0.00029 (p<0.05). The results of the community service show that there is a significant difference between the average pre-test and post-test results. Conclusion: The community service activities carried out at SMP 8 Muhammadiyah Surakarta succeeded in increasing students' knowledge about breast cancer and the importance of early detection through the breast self-examination method (SADARI).